Impact of Foncodes on rural enterprises that change lives in Peru - Wong Copaja, Edgard Enrique (2024)
Today, governments see entrepreneurship as a means to promote the economic, social, productive and even cultural development of their countries, but despite the benefits of this trend, there are still many important challenges that must be overcome for the benefits of entrepreneurship to be truly sustainable and long-lasting (Jurado, 2022). This is the problem that Foncodes considers necessary to address: the limited access of subsistence families to local markets in densely populated rural Andean and jungle areas. The challenge is to overcome the underlying causes, namely limited technical knowledge of family production in rural areas, lack of capitalization of family assets, and poor knowledge of input and service markets and product destinations, through the creation of agricultural and non-agricultural enterprises in high mountain and jungle areas, managed by rural subsistence farmers, organized according to a basic implementation model and using Foncodes financial resources. From 2012 to August 2023, Foncodes financed 16,261 enterprises, with the amount financed being S/169,700,250. As main results, 97% of the implemented enterprises were operational and users in the jungle increased their income by 60.95% and those in the highlands by 72.08%, also 45.59% of ERI participate in expanded markets; allowing the generation and/or preservation of 63,273 family self-employment.